1996
DOI: 10.1111/j.1476-5381.1996.tb15173.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabotropic glutamate receptors, transmitter output and fatty acids: studies in rat brain slices

Abstract: The effects of (1S,3R)‐1‐aminocyclopentane‐1,3‐dicarboxylic acid (1S,3R‐ACPD), a non‐selective agonist of the metabotropic glutamate receptors (mGluRs), have been studied in rat cortical and striatal slices by measuring the depolarization‐induced output of D‐[3H]‐aspartate (D‐[3H]‐Asp) and of [3H]‐glutamate ([3H]‐Glu), neosynthesized from [3H]‐glutamine. In cortical slices, 1S,3R‐ACPD potentiated the depolarization‐induced (KCl, 30 mM) output of both D‐[3H]‐Asp and [3H]‐Glu. The potentiation, obtained at 300 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Although these results at first seem to concur with the studies showing augmentation of glutamate release in synaptosomal preparations in the presence of low concentrations of arachidonic acid, different stimuli were used by the two groups to evoke neurotransmitter release. Although Lombardi et al (1994, 1996) used 30 m M KCl in their study, this clamped depolarization was found to be unresponsive to either 1 S ,3 R ‐ACPD or protein kinase C manipulation in the Herrero et al (1992) study using synaptosomes. However, this discrepancy might be due to time‐course or methodological differences, such as measurement of prelabeled versus endogenous amino acids or the use of different preparations (Lombardi et al, 1993, 1994, 1996).…”
Section: Glutamate/aspartatementioning
confidence: 93%
See 2 more Smart Citations
“…Although these results at first seem to concur with the studies showing augmentation of glutamate release in synaptosomal preparations in the presence of low concentrations of arachidonic acid, different stimuli were used by the two groups to evoke neurotransmitter release. Although Lombardi et al (1994, 1996) used 30 m M KCl in their study, this clamped depolarization was found to be unresponsive to either 1 S ,3 R ‐ACPD or protein kinase C manipulation in the Herrero et al (1992) study using synaptosomes. However, this discrepancy might be due to time‐course or methodological differences, such as measurement of prelabeled versus endogenous amino acids or the use of different preparations (Lombardi et al, 1993, 1994, 1996).…”
Section: Glutamate/aspartatementioning
confidence: 93%
“…Although Lombardi et al (1994, 1996) used 30 m M KCl in their study, this clamped depolarization was found to be unresponsive to either 1 S ,3 R ‐ACPD or protein kinase C manipulation in the Herrero et al (1992) study using synaptosomes. However, this discrepancy might be due to time‐course or methodological differences, such as measurement of prelabeled versus endogenous amino acids or the use of different preparations (Lombardi et al, 1993, 1994, 1996). In particular, there is likely to be a considerable involvement of glial cells in the responses in brain slices, but not the synaptosome preparations (Winder and Conn, 1996).…”
Section: Glutamate/aspartatementioning
confidence: 93%
See 1 more Smart Citation
“…Presynaptic mGluRs regulating the release of excitatory amino acids have been demonstrated in in vitro release studies in various brain slice and synaptosomal preparations (Herrero et al, 1994;Lombardi et al, 1994Lombardi et al, , 1996East et al, 1995). The presynaptic mGluRs are likely to be localized on glutamatergic vagal afferent terminals in the nucleus tractus solitarii (Lawrence and Jarrott, 1994), whereas postsynaptic mGluRs could be associated with GABAergic interneurons (Glaum and Miller, 1993a;Beart et al, 1994) or aspartateutilizing neurons/terminals (Beart et al, 1994) in the nucleus tractus solitarii.…”
Section: Discussionmentioning
confidence: 99%
“…Cortical-subcortical coronal frontal slices (anteriorly to the lateral ventricles) were then cut at a thickness of 200 m with a Leica VT1000S vibratome and maintained at 32°C for 30 min to allow functional recovery and later kept at 25°C in the same buffer. Recovered slices were transferred in a perfusion chamber and perfused (1 ml/min) at room temperature for 5 min, 20 min, or 1 h with a gassed (95% 0 2 /5% CO 2 ) solution (1.25 mM KH 2 PO 4 , 1.3 mM MgSO 4 , 2.5 mM CaCl 2 , 17.6 mM NaHCO 3 , 10 mM D-glucose, pH 7.4) containing isomolar low or high [K ϩ ] (125 mM NaCl, 3 mM KCl or 98 mM NaCl, 30 mM KCl, respectively) in accordance with a previously published protocol (14). After perfusion, the slides were rapidly lysed in a potter with 200 l of lysis buffer (50 mM Tris-HCl, pH 7.4, 150 mM NaCl, 1% Triton X-100, 2 mM EDTA, 1 mM DTT, 1 mM PMSF, 1 mM NaF, 1 mM Na 3 VO 4 , phosphatase inhibitor mixture (Roche), and protease inhibitor mixture (Sigma)).…”
Section: Methodsmentioning
confidence: 99%